APPROACHES TO ENHANCE ENGLISH SPEAKING SKILLS AMONG ENGINEERING GRADUATES THROUGH JAM SESSION IN A MIXED CLASSROO - Batool Fatima Khaleel, Dr. K B Glory, K Sree Vasudha, Md Shahida Sultana (International Journal of Advanced Science and Technology, 2020)
Communication skills are essential to increasing the employability of engineering graduates. It isobserved that majority of engineering graduates lack speaking skills. Sufficient guidance should beprovided to students in the direction of workplace communication. Thus, universities need to review thelanguage and communication courses and teaching methods to reach and surpass the needs of allstakeholders. Therefore, taking these challenges into account, this paper focuseson the importance of English speaking skills among engineering graduates in a mixed classroom, and thechallenges they face in both academic and professional life and their potential remedies. The pre-test andpost-test were performed on 30 engineering students to assess their speaking ability levels. The findingsindicate a substantial increase in their oral competency. The aim of the paper is to develop the oralcompetency of students through Impromptu or JAM session speaking activity.